Thermal, Structural Properties and Potential Dynamic Corrosion Study of Ti-27Ni-21Nb-2Ta SMA - Balci, Esra; Dagdelen, Fethi (Springer Int Publ Ag, 2022)
In this study, Ti-27Ni-21Nb-2Ta (at. %) alloy was produced by arc-melting method. The physical and chemical properties of the alloys such as phase transformation temperatures, thermal activation energies, microstructure, electrochemical resistance, microhardness were investigated. Phase transformation temperatures were determined by DSC. The thermal activation energies of the alloy were calculated according to the Ozawa, Kissenger, and Takhor methods. The average thermal activation energy obtained according to these calculations was 56.35 kJ/mol. The optical microscope (OM) and SEM images showed that the alloy consisted of a dendritic structure. beta-Nb, B2, and B19' peaks were found in the XRD pattern. Additionally, the crystallite size calculated by the Scherrer equation was estimated to be approximately 29.86 nm. Electrochemical investigation performed in SBF (artificial body fluid) at room temperature (RT) yielded a corrosion resistance rate of 9.38 x 10(-6) mmpy analysis. The microhardness measurement of the alloys was taken from five distinct regions with an average of 376 HV0.3.
Keywords: Shape memory alloys; Thermal activation energy; Corrosion resistance rate; Microhardness